지방자치단체 갈등관리 분야 법규 분석 - 변성수(Sung Soo Byun); 류상일(Sang Il Ryu); 최호택(Ho Taek Choi) (한국콘텐츠학회 논문지, 9(12), 2009)
This paper as basic study for the effective conflict management of the local government analyzed the local laws and regulations in conflict. The significant analysis details of this research are a basic contents, a goal and conflict party, a term of the laws and regulations and an consideration committee, an mediation committee, a important different item. And this research suggests that the improvement of he local laws and regulations in conflict are the local government chief's understand change about conflict management, strengthening a role of the conflict management organization and an implementation of agreement subject, the spread of a administrative and financial support clauses. 이 연구는 지방자치단체의 효율적인 갈등관리를 위한 기초연구로서, 갈등관리 분야의 법규에 관한 내용을 분석하였다. 이를 통하여 효율적인 갈등관리를 위한 법규의 개선방안을 모색하고자 하였다. 이 연구의 주요 분석내용은 법규의 기초 사항, 목적 및 갈등당사자, 용어, 심의기구, 조정기구, 중요 특이 사항 등을 포함하고 있다. 그리고 이 연구는 갈등관리 분야 법규의 개선방안으로서 자치단체장의 갈등관리에 대한 인식 전환 및 의지 강화, 갈등관리기구의 역할과 심의 조정 내용의 반영 및 이행 강화, 행 재정적 지원 규정의 확산 등을 제시하고 있다.